Optophysiological analysis of associational circuits in the olfactory cortex - Hagiwara, Akari; Pal, Sumon K.; Sato, Tomokazu F.; Wienisch, Martin; Murthy, Venkatesh N. (Frontiers in Neural Circuits, 2012)
Primary olfactory cortical areas receive direct input from the olfactory bulb, but also have extensive associational connections that have been mainly studied with classical anatomical methods. Here, we shed light on the functional properties of associational connections in the anterior and posterior piriform cortex (aPC and pPC) using optophysiological methods. We found that the aPC receives dense functional connections from the anterior olfactory nucleus (AON), a major hub in olfactory cortical circuits. The local recurrent connectivity within the aPC, long invoked in cortical autoassociative models, is sparse and weak. By contrast, the pPC receives negligible input from the AON, but has dense connections from the aPC as well as more local recurrent connections than the aPC. Finally, there are negligible functional connections from the pPC to aPC. Our study provides a circuit basis for a more sensory role for the aPC in odor processing and an associative role for the pPC.